Method for the simultaneous labelling of terminal deoxynucleotidyl transferase (TdT) and membrane antigens. Issue 6 (June 1984) - Tavares de Castro, J; San Miguel, J F; Soler, J; Catovsky, D
Abstract : A method for the simultaneous labelling of terminal deoxynucleotidyl transferase (TdT) and membrane antigens is described. TdT is visualised in the cell nucleus with the peroxidase-antiperoxidase (PAP) method, and the immunogold method is used in combination with monoclonal antibodies against membrane antigens. The morphology of the labelled cells is well preserved for analysis by light microscopy and the preparations obtained can be kept permanently. This method is useful for the analysis of mixed cell proliferations, particularly in leukaemias.